2021
DOI: 10.4317/jced.56467
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of maxillary sinus septa in a brazilian population

Abstract: Background The aim of this study was to assess the anatomic aspects of the maxillary sinus septa, by means of computed tomography images, in a Brazilian population. The results might be of clinical significance in sinus lift surgery planning. Material and Methods In the study, 123 computed tomographs obtained from a private radiology clinic were used. They were analyzed by a single, trained and calibrated observer in order to evaluate the presence, quantity, localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
9
3
0
Order By: Relevance
“…This was in agreement with several other studies; for example, Furtado and his colleagues found the highest percentage of septa to be in the middle sinus region (44.2%) (45), while Toprac and Atac found it was 59.62% (43), and the Orhan group reported 69.1% (37). Meanwhile, contradictory results were also reported by Schriber and his group, who found the majority of septa to be located in the posterior maxilla in the region of the second molars (47), whereas Shahidi et al found most septa were in the anterior region (Shahidi et al 2016) and (48) reported no signi cant difference among the locations of septal occurrence in the anteroposterior plane (48).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was in agreement with several other studies; for example, Furtado and his colleagues found the highest percentage of septa to be in the middle sinus region (44.2%) (45), while Toprac and Atac found it was 59.62% (43), and the Orhan group reported 69.1% (37). Meanwhile, contradictory results were also reported by Schriber and his group, who found the majority of septa to be located in the posterior maxilla in the region of the second molars (47), whereas Shahidi et al found most septa were in the anterior region (Shahidi et al 2016) and (48) reported no signi cant difference among the locations of septal occurrence in the anteroposterior plane (48).…”
Section: Discussionsupporting
confidence: 93%
“…Comparing the occurrence of septa in the right versus the left sinuses revealed no signi cant difference, which was in accordance with (45), where no statistically signi cant difference was detected when evaluating both sides (p > 0.05). In contrast, some differences were reported in other studies with no clear explanation for the reasons (37) Our study presented a lower number of subjects with bilateral septa (only 35.25% of all patients with septa had them bilaterally).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Comparing the occurrence of septa in the right versus the left sinuses revealed no significant difference, which was in accordance with [ 48 ], where no statistically significant difference was detected when evaluating both sides ( p > 0.05). In contrast, some differences were reported in other studies with no clear explanation for the reasons [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Due to the continuous gasification and expansion of the maxillary sinus, the distance between the top of the maxillary alveolar ridge and the bottom wall of the maxillary sinus is reduced, and the bone is more porous, resulting in a lower height of the remaining alveolar bone in the implant area, which is prone to atrophy, thus increasing the difficulty of dental implants [ 9 , 10 ]. In recent years, the maxillary sinus lift has had a good clinical effect on the implant restoration of the maxillary posterior region.…”
Section: Discussionmentioning
confidence: 99%